Penulisan Naskah Film Dokumenter “Thread by Thread: Mengurai Krisis Fast Fashion di Indonesia” melalui Pendekatan Narasi Ekspositoris Struktur 3 Babak - Aura Diva Rizky; Muh. Fadli Rumpak; Nurmaya Prahatmaja; Rinda Aunillah Sirait (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The documentary film “Thread by Thread: Mengurai Krisis Fast Fashion di Indonesia” is a 14-minute film that explores the environmental and social impacts of the fast fashion industry in Indonesia, along with the low public awareness of this issue. It highlights problems such as textile waste, labor exploitation, and the role of social media in reinforcing consumerist culture. “Thread by Thread” is designed as an educational tool to enhance public literacy and encourage more responsible and sustainable fashion consumption. During its creation, the writer served as the scriptwriter, responsible for crafting a factual and systematic narrative using an expository approach structured into three acts. Act I presents the factual context of fast fashion in Indonesia; Act II discusses its negative environmental impacts and the controversy over thrifting as an alternative solution, supported by data and interviews; and Act III offers sustainability-based solutions with an appeal for audiences to be critical and responsible in their fashion choices.